Impact of seasonal variation on endocrine profile during an estrous cycle in dairy cows - Kumar, Harish; Kumar, Pravesh; Sharma, Akshay; Dr. Rajesh Chahota; Sharma, Pururava (Indian Journal of Dairy Science, 2023)
The objective of the study was to investigate the influence of season viz., summer, winter, and isothermic (spring and autumn season), on endocrine profile in dairy cows. The daily temperature-humidity index (THI) was recorded using a dry and wet-bulb thermometer to envisage its variation among different seasons. For analysis of endocrine profile, blood samples were collected from thirty dairy cows (n=10 in each season) at 5-day interval i.e. day 0 (day of estrus) to day 20, of the estrous cycle for ELISA based estimation of estradiol-17β, progesterone, and cortisol. In results, the THI varied significantly (p